2022
DOI: 10.3390/vaccines11010046
|View full text |Cite
|
Sign up to set email alerts
|

Social Support Mediates the Relationship between COVID-19-Related Burnout and Booster Vaccination Willingness among Fully Vaccinated Nurses

Abstract: COVID-19 booster doses for high-risk groups such as nurses are necessary to reduce the impacts of the pandemic and promote public health. We examined the relationship between COVID-19-related burnout and booster vaccination willingness among nurses, and we assessed whether social support can buffer this relationship. We conducted a cross-sectional study with 963 fully vaccinated nurses working in healthcare settings in Greece. We used the multidimensional scale of perceived social support to measure social sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 73 publications
(94 reference statements)
1
7
0
Order By: Relevance
“…34 However, later studies in Greece that were conducted during September-October 2022 found significant lower vaccination acceptance even among nurses. In particular, in a sample from the general population 34.1% reported being very likely to be vaccinated with a booster dose, 24 while among nurses the respective percentage was slightly higher (37.1%) 35 . Moreover, low levels of seasonal influenza vaccine intention among nurses in Greece for the 2022/2023 season (57.3%) are an alarmed sign of vaccine hesitancy in the country.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…34 However, later studies in Greece that were conducted during September-October 2022 found significant lower vaccination acceptance even among nurses. In particular, in a sample from the general population 34.1% reported being very likely to be vaccinated with a booster dose, 24 while among nurses the respective percentage was slightly higher (37.1%) 35 . Moreover, low levels of seasonal influenza vaccine intention among nurses in Greece for the 2022/2023 season (57.3%) are an alarmed sign of vaccine hesitancy in the country.…”
Section: Discussionmentioning
confidence: 90%
“…Earlier studies in Greece confirm this finding including samples from the general population and nurses. 24,35 No other studies has investigated until now this relationship throughout the world. Although we cannot make direct comparisons with other studies, we should notice that three years after the onset of the COVID-19 pandemic it is quite probable that people experience burnout.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Another study reported that social support partially mediated the relationship between COVID-19 related burnout and willingness of booster vaccination in a group of fully vaccinated nurses in Greece. 16 Influence of social support networks on hesitancy toward COVID-19 vaccination was also found in a qualitative study on older adults in Hong Kong. 17 Though these studies provide important insights on the association between social support and vaccine uptake, a common limitation of all these studies is that they were conducted on very specific groups (e.g., nurses in a healthcare facility), and the findings thereby were not generalizable.…”
Section: Introductionmentioning
confidence: 80%
“…The improvement of knowledge among health workers and encouragement of more active and problem-based coping mechanisms can reduce mental disorder rates and improve the efficiency of health care services (15). It has been demonstrated that social support, the facilitation of communication through social media, and planning for the reduction of perceived stigma, as well as immunization awareness programs, especially during a pandemic, can help reduce burnout's psychological consequences (27,28).…”
Section: Discussionmentioning
confidence: 99%